2021
DOI: 10.3389/fimmu.2021.734008
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization and Plasticity in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that attacks almost every organ. The condition mostly happens to adults but is also found in children, and the latter have the most severe manifestations. Among adults, females, especially non-Caucasian, are mostly affected. Even if the etiology of SLE remains unclear, studies show a close relation between this disease and both genetics and environment. Despite the large number of published articles about SLE, we still do not have a clear picture of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 133 publications
(149 reference statements)
0
30
0
Order By: Relevance
“…Mtb can activate infected Mphs and thus change the cytokines and chemokine production. The ESAT-6 (early Secreted Antigenic Target 6 kDa) is thought to be one of the Mtb factors inducing the proinflammatory M1 phenotype at the start of the infection, which facilitates granuloma formation and then switches M polarization from M1 to M2 at a later stage of the infection [155].…”
Section: Macrophage Polarization Programsmentioning
confidence: 99%
“…Mtb can activate infected Mphs and thus change the cytokines and chemokine production. The ESAT-6 (early Secreted Antigenic Target 6 kDa) is thought to be one of the Mtb factors inducing the proinflammatory M1 phenotype at the start of the infection, which facilitates granuloma formation and then switches M polarization from M1 to M2 at a later stage of the infection [155].…”
Section: Macrophage Polarization Programsmentioning
confidence: 99%
“…The number of decidual effector Treg cells was reduced in patients with early miscarriage ( 64 ), and clonally expanded effector Treg cells were significantly reduced in patients with PE ( 65 ), as compared to normal pregnancies. Macrophages were classically polarized into classically activated macrophages (M1) and alternatively activated macrophages (M2) in response to stimulation by different immune microenvironments ( 66 ). Studies ( 67 , 68 ) had shown that a decrease in the proportion of M2-like macrophages and an increase in total macrophages was detrimental to embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated the role of macrophages in the pathogenesis of SLE. Additionally, experiments have increasingly reported a close relationship between SLE and macrophages [ 59 , 60 ]. Conversely, blocking macrophage activation alleviates the progression of SLE, suggesting that apoptotic double-stranded DNA-induced macrophage activation may play an important pathogenic role in the development of SLE [ 56 ].…”
Section: Discussionmentioning
confidence: 99%